The Correlation Between Students’ Vocabulary Mastery and Speaking Mastery - Anry Ani; Yusni Sinaga (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2021)
The purpose of the research was to know the correlation between vocabulary mastery and speaking mastery at grade VIII students of SMP N 5 Padangsidimpuan. Type of this research was quantitative research with a correlational method. Based on calculation of the data, the researcher found that the score of rxy was more than rtable 0.737 0,423. It means the result showed that there was a significant correlation between two variables in the good category.